The service culture handbook a step-by-step guide to getting your employees obsessed with customer service - Toister, Jeff (Findaway World, 2020)
Imagine you could develop a customer-focused culture so powerful that your employees always seem to do the right thing. They encourage each other, proactively solve problems, and constantly look for ways to go the extra mile. In short, imagine a workplace culture where employees were absolutely obsessed with customer service. The Service Culture Handbook is a step-by-step guide to help you develop a customer-focused culture in your company, department, or location. Whether you're just beginning your journey, or have been working on culture for years, this handbook will prepare you to take the next step. You'll receive actionable advice, straightforward exercises, and proven tools you can utilize immediately. Learn the one thing that forms the foundation of every great culture. Discover what customer-focused companies do differently to engage their employees. And explore ways to strategically align every facet of your organization with outstanding service. Creating and sustaining a customer-focused culture is a never-ending journey that takes hard work, dedication, and commitment. The Service Culture Handbook is an indispensable resource to help you and your employees stay headed in the right direction.
Online resource; title from cover image (EBSCO, viewed May 6, 2020)
Keywords: Customer services; Consumer satisfaction; Corporate culture; Service à la clientèle; Consommateurs; Satisfaction; Culture d'entreprise; Downloadable audio books; Audiobooks; Livres audio